Challenges and prospects of establishing a Muslim University in Nigeria - Rufai, Saheed Ahmad; Adedeji, Luqman ‘Lekan (Faculty of Education, U.K.M, 2011)
Nigeria is currently witnessing an unprecedented proliferation of universities owing to the active involvement of the private sector in university education in the country. This development has culminated in an incredible increase in the number of religious organizations that are granted licences to establish and operate private universities in the country. However, the Nigerian Muslims have remained at a receiving end owing to the pervasive pessimism among them over the likelihood of their failure in any attempt or move towards seeking to own a university of their own. Their pessimism itself is a product of the general perception that the establishment of a university in Nigeria is capital intensive as they wonder whether there are prospects for such a venture. The purpose of this paper is to articulate the challenge and prospects of founding a Muslim university in contemporary Nigeria. Relying on data from the ongoing developments concerning the participation of the private sector in the provision of university education, this paper provides a rationale for such an endeavour among Muslims and enumerates the immense benefits and opportunities that will be brought about by such Muslim venture